2017
DOI: 10.1038/ncomms15725
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte adaptive immunity mediates diet-induced adipose inflammation and insulin resistance by decreasing adipose Treg cells

Abstract: Obesity leads to a switch in subsets of CD4+ T cell in adipose tissue, characterized by an increase in IFNγ producing Th1 cells and a decrease in anti-inflammatory regulatory T (Treg) cells, which impairs systemic insulin sensitivity. What signals these changes is unknown. Herein we demonstrate that genetic deficiency of adipocyte MHCII decreases adipose IFNγ expression and increases adipose Treg abundance in obese mice, leading to reduced obesity-induced adipose inflammation and reduced insulin resistance wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(101 citation statements)
references
References 46 publications
5
96
0
Order By: Relevance
“…By contrast to uninfected monkeys, adipose tissue T cells also expressed higher levels of HLA.DR indicating increased activation compared to blood T cells, yet Ki67 levels were similar between blood and adipose-resident T cells [37]. Tregs in adipose tissue are reduced in obese humans and mice, but in cART-treated HIV patients, Damouche et al observed an increase in CD4+CD25+Foxp3+ Tregs and a higher Treg/Th17 ratio in subcutaneous adipose tissue compared to uninfected subjects [6164]. Intriguingly, CD4 T cells in adipose tissue of HIV patients also had increased expression of PD-1 compared to blood CD4 T cells, indicating the potential immune exhaustion of adipose-resident T cells, and it was suggested that these cells may harbor latent HIV [61].…”
Section: Composition and Functions Of Immune Cells In Adipose Tissue mentioning
confidence: 99%
“…By contrast to uninfected monkeys, adipose tissue T cells also expressed higher levels of HLA.DR indicating increased activation compared to blood T cells, yet Ki67 levels were similar between blood and adipose-resident T cells [37]. Tregs in adipose tissue are reduced in obese humans and mice, but in cART-treated HIV patients, Damouche et al observed an increase in CD4+CD25+Foxp3+ Tregs and a higher Treg/Th17 ratio in subcutaneous adipose tissue compared to uninfected subjects [6164]. Intriguingly, CD4 T cells in adipose tissue of HIV patients also had increased expression of PD-1 compared to blood CD4 T cells, indicating the potential immune exhaustion of adipose-resident T cells, and it was suggested that these cells may harbor latent HIV [61].…”
Section: Composition and Functions Of Immune Cells In Adipose Tissue mentioning
confidence: 99%
“…14 These data have also been supported by results from studies showing that several other VAT immunocytes exert their effect on metabolic parameters through modulation of VAT Tregs; for example, iNKT cells sustain VAT Tregs to promote insulin sensitivity, 33 and IFN-γ-producing Th1 cells inhibit VAT Tregs to drive insulin resistance. 34 Mechanistically, both immunocytes and adipocytes are modulated by VAT Tregs. As concerns immunocytes, VAT Tregs play a critical role in keeping a balance between anti-inflammatory and pro-inflammatory macrophages, promoting differentiation of the former while suppressing the latter.…”
Section: Fun C Tionmentioning
confidence: 99%
“…25 On the contrary, adipocyte-specific MHCII-deficient mice exhibit significantly reduced IFN-γ production in VAT on HFD and correspondingly elevated numbers of VAT Tregs. 34 It is not entirely clear whether the effect of IFN-γ on VAT Tregs is due to Treg-intrinsic mechanisms or rather to modulation of the numbers of ILC2s, which may promote Treg accumulation through the ICOS-ICOSL axis. 25 In addition to these factors, Rab4-B, a small GTPase controlling endocytic trafficking, is reduced in VAT T cells from obese individuals and may also contribute to the reduction in VAT Tregs during obesity.…”
Section: Sex and Depotmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33] Adipose Treg cells are induced upon several metabolic and environmental stimuli and have been suggested to control adipocyte function through a signal transducer and activator of transcription 6-phosphatase and tensin homologue axis. 34 On the other hand, adipocytes can regulate T-cell fate through major histocompatibility complex class II-dependent secretion of interferon-c. 35 However, the regulation of adipose-derived metabolites of T-cell differentiation remains largely unanswered.…”
Section: Fatty Acids In the Bone Marrow To Support Long-lived Immune mentioning
confidence: 99%